1996
DOI: 10.1037/0022-0167.43.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of session length on treatment outcome for college students in brief therapy.

Abstract: Ninety-four college students were examined to investigate the effects of session length (30and 50-min "hours") on therapy success. A prescreening assessment consisting of the Minnesota Multiphasic Personality Inventory-2 and the College Adjustment Scale was conducted. Therapy was provided by either a licensed psychologist, social worker, or marriage and family counselor trained in brief therapy. On completion of a maximum of 8 therapy sessions, client adjustment and satisfaction were assessed. No difference wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…A comparison group of students who did not receive counselling exhibited minimal change over the same period of time. Turner et al (1996) found that time-limited counselling had a modest impact on adjustment in a sample of student clients. Vonk & Thyer (1999), in a study of the effectiveness of short-term counselling (average 10 sessions), found that, compared to students in a waiting-list condition, those who received counselling recorded substantial levels of clinical improvement.…”
Section: College and Student Counsellingmentioning
confidence: 99%
“…A comparison group of students who did not receive counselling exhibited minimal change over the same period of time. Turner et al (1996) found that time-limited counselling had a modest impact on adjustment in a sample of student clients. Vonk & Thyer (1999), in a study of the effectiveness of short-term counselling (average 10 sessions), found that, compared to students in a waiting-list condition, those who received counselling recorded substantial levels of clinical improvement.…”
Section: College and Student Counsellingmentioning
confidence: 99%
“…Indeed, brief therapy has been hailed as the "model of choice" (Archer & Cooper, 1998, p. 25) for college counseling centers. Furthermore, studies conducted in university counseling centers attest to the interest in brief therapy (Regan & Hill, 1992;Turner, Valtierra, Talken, Miller, & DeAnda, 1996). Counseling centers are strategically positioned for the use of techniques that facilitate rapid change.…”
Section: Client Population and Settingmentioning
confidence: 99%
“…In spite of this growing need, very few empirical evaluations of student counseling centers have been published over the past 25 years (Gelso, Spiegel, & Mills, 1983;Harman, 1971;Keilson, Dworkin, & Gelso, 1983;Turner, Valtierra, Talken, Miller, & DeAnda, 1996). Of the small number of evaluations that are available, only four have been identified that are focused specifically on short-term treatment outcome.…”
mentioning
confidence: 99%
“…The main disadvantage of their study was the exclusion of clients who were outside the normal to moderately disturbed range, a group who is being treated at counseling centers in increasing numbers. Turner et al (1996) used the MMPI-2, the College Adjustment Scale, and the Client Satisfaction Questionnaire for pre-and posttreatment testing of 94 college students randomly assigned to either 30-minute session or 50-minute session therapy. Both groups improved equivalently.…”
mentioning
confidence: 99%
See 1 more Smart Citation